2018
DOI: 10.1007/s00436-018-5835-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking to Toxoplasma gondii thymidylate synthase-dihydrofolate reductase and efficacy of raltitrexed in infected mice

Abstract: Toxoplasmosis is a zoonosis of worldwide distribution. Currently, two drugs, pyrimethamine and sulfadiazine, are used as a reference in the treatment of toxoplasmosis, but the resistance of Toxoplasma gondii appears as a relevant public health problem. In order to identify new drugs to toxoplasmosis treatment, we performed a molecular docking of raltitrexed to T. gondii thymidylate synthase-dihydrofolate reductase (TS-DHFR) and also evaluated its efficacy in infected mice. Initially, raltitrexed was docked on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…T. gondii has a number of viable targets that can be inhibited by several drugs [ 39 , 40 ]. Thymidylate synthase-dihydrofolate reductase (TS-DHFR) was selected as a target for drugs that can eradicate this parasite [ 41 , 42 , 43 ] and 1UE ligand (the co-crystalized ligand inside active site) was chosen as a positive control compound. According to what was previously published, we found that there is a direct relationship between the inhibition of cyclin dependent kinase 2 (CDK2) and flavonoids in cancer therapy [ 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…T. gondii has a number of viable targets that can be inhibited by several drugs [ 39 , 40 ]. Thymidylate synthase-dihydrofolate reductase (TS-DHFR) was selected as a target for drugs that can eradicate this parasite [ 41 , 42 , 43 ] and 1UE ligand (the co-crystalized ligand inside active site) was chosen as a positive control compound. According to what was previously published, we found that there is a direct relationship between the inhibition of cyclin dependent kinase 2 (CDK2) and flavonoids in cancer therapy [ 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%